2015
DOI: 10.1186/s13071-015-1015-y
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of the species of hookworms infecting dogs in Central Vietnam

Abstract: BackgroundDifferentiation of canine hookworm species is crucial from both a veterinary and public health standpoint. In Vietnam, three hookworm species, namely Ancylostoma caninum, Ancylostoma braziliense and Uncinaria stenocephala are reported to infect dogs. In light of the emerging distribution of A. ceylanicum in Asia, this study aims to re-evaluate the status of Ancylostoma in dogs in Vietnam.MethodsFaecal samples collected from 200 community dogs in Dak Lak province were subjected to faecal floatation fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…For this, molecular tools are more appropriate [ 20 ]. Second, various studies have identified hookworm species separately across humans [ 19 , 21 , 22 ], dogs [ 23 , 24 , 25 ] or soil [ 26 ], but to our knowledge there are no studies which have identified hookworm species using molecular techniques within both hosts and environment in the same geographical region. The present study aims at molecular identification of hookworms isolates from humans, dogs and soil from a tribal area in Tamil Nadu, India.…”
Section: Introductionmentioning
confidence: 99%
“…For this, molecular tools are more appropriate [ 20 ]. Second, various studies have identified hookworm species separately across humans [ 19 , 21 , 22 ], dogs [ 23 , 24 , 25 ] or soil [ 26 ], but to our knowledge there are no studies which have identified hookworm species using molecular techniques within both hosts and environment in the same geographical region. The present study aims at molecular identification of hookworms isolates from humans, dogs and soil from a tribal area in Tamil Nadu, India.…”
Section: Introductionmentioning
confidence: 99%
“…Humans can be infected via contact with a dog or cat or via contamination of infective stages in food or water [20, 35]. Worldwide, there is a significant variation in the prevalence of gastrointestinal zoonotic helminths in dogs and cats [19, 24]. High infection rates of zoonotic parasites including hookworms, Trichuris spp., Spirometra spp., Taenia spp., Toxocara spp.…”
mentioning
confidence: 99%
“…A . ceylanicum is commonly found in dogs and cats in Asia, and high rates of infection with that species in domestic, stray, and community-raised dogs and cats have been reported in Malaysia [ 3 ], Laos [ 5 ], India [ 15 , 16 ], Thailand [ 6 , 7 , 17 ], Cambodia [ 8 ], Vietnam [ 18 ], Indonesia [ 19 ], and southern China [ 20 ]. In addition, infections in dogs as well as humans have also been reported in the Solomon Islands [ 21 , 22 ] and northern Australia [ 23 – 27 ].…”
Section: Discussionmentioning
confidence: 99%